Corrosion-resistant material for preparing wafer chuck and preparation method of corrosion-resistant material

By introducing a combination of polyvinylidene fluoride grafted with perfluorohexyl side chains and modified boron nitride and silicon carbide into the wafer chuck material, the problem of insufficient corrosion resistance of wafer chucks in acidic and alkaline environments is solved, achieving high corrosion resistance and cost-effectiveness of the material.

CN120966181APending Publication Date: 2025-11-18QINGDAO BESLAN SEMICONDUCTOR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511330850.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2025-11-18

AI Technical Summary

Technical Problem

Existing wafer chuck materials have insufficient corrosion resistance in acidic and alkaline environments and are relatively expensive, which limits their large-scale promotion and use.

Method used

Polyvinylidene fluoride grafted with perfluorohexyl side chains is used as the matrix and combined with modified boron nitride and modified silicon carbide. The surface energy and chemical stability of the material are improved by grafting the perfluorohexyl side chains. Modified boron nitride and silicon carbide are uniformly dispersed in the polyvinylidene fluoride matrix to construct a multi-layer barrier structure to improve corrosion resistance.

Benefits of technology

It significantly improves the material's resistance to acid and alkali corrosion and its corrosion resistance, extends the service life of wafer chucks, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005601106080000121
    Figure BDA0005601106080000121
  • Figure BDA0005601106080000131
    Figure BDA0005601106080000131
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant material for preparing a wafer chuck and a preparation method of the corrosion-resistant material, and belongs to the technical field of corrosion-resistant materials. The corrosion-resistant material for preparing the wafer chuck is prepared from the following raw materials in parts by weight: 70 to 90 parts of polyvinylidene fluoride grafted with a perfluorohexyl side chain, 5 to 15 parts of modified boron nitride and 5 to 15 parts of modified silicon carbide, the polyvinylidene fluoride grafted with the perfluorohexyl side chain is prepared by taking a monomer containing the perfluorohexyl side chain as a grafting monomer and grafting the perfluorohexyl side chain to the polyvinylidene fluoride. Polyvinylidene fluoride grafted with a perfluorohexyl side chain is used as a matrix, the tolerance and corrosion resistance of the material to acid and alkali can be effectively improved, and modified boron nitride and modified silicon carbide have good compatibility with the polyvinylidene fluoride grafted with the perfluorohexyl side chain. The modified boron nitride and the modified silicon carbide are uniformly dispersed in a polyvinylidene fluoride base grafted with a perfluorohexyl side chain, and the corrosion resistance of the material is improved through the combined action of the three components.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a corrosion-resistant material for preparing a wafer chuck and a preparation method thereof, and belongs to the technical field of corrosion-resistant materials. BACKGROUND

[0002] The wafer chuck is a device used for fixing and supporting a wafer in a semiconductor manufacturing process, and ensures that the wafer can maintain a stable and accurate position during processing. It not only needs to provide stable support for the wafer, but also needs to ensure high-precision positioning and stable operation during various processing processes (such as cleaning, etching, etc.). However, during these processing processes, the wafer chuck inevitably comes into frequent contact with cleaning liquid, etching liquid and other chemicals, which often contain corrosive components such as acid and alkali. Therefore, the wafer chuck not only needs to have good mechanical properties, but also has a very high requirement for the corrosion resistance of the material.

[0003] In the prior art, PTFE (polytetrafluoroethylene) and FCTFE (polychlorotrifluoroethylene) are usually used to prepare the wafer chuck. Although the two materials have excellent corrosion resistance and good resistance to chemicals, their high cost limits their large-scale promotion and utilization to some extent.

[0004] Polyvinylidene fluoride mainly refers to polyvinylidene fluoride homopolymer or copolymer of polyvinylidene fluoride and a small amount of other fluorine-containing vinyl monomers. It has the characteristics of fluororesin and general resin. In addition to good chemical corrosion resistance, high temperature resistance, oxidation resistance, weather resistance, and radiation resistance, it also has piezoelectricity, dielectricity, thermoelectricity and other special properties, and the relative price is relatively low. However, its corrosion resistance is limited, and its pH tolerance range is 2-10, which is difficult to be used in environments with high acidity and high alkalinity for a long time.

[0005] Therefore, it is necessary to provide a corrosion-resistant material for preparing a wafer chuck, which can take into account acid and alkali resistance, corrosion resistance, cost and other factors, and realize reliable operation and long service life of the wafer chuck in a complex chemical corrosion environment. SUMMARY

[0006] In order to solve the above problems, a corrosion-resistant material for preparing a wafer chuck and a preparation method thereof are provided. The raw material of the corrosion-resistant material for preparing the wafer chuck is limited, and polyvinylidene fluoride grafted with a perfluorohexyl side chain is used as a matrix. The material can effectively improve the acid and alkali resistance and corrosion resistance of the material. Modified boron nitride and modified silicon carbide have good compatibility with polyvinylidene fluoride grafted with a perfluorohexyl side chain. Modified boron nitride and modified silicon carbide are uniformly dispersed in the polyvinylidene fluoride matrix grafted with a perfluorohexyl side chain. The three together improve the corrosion resistance of the material.

[0007] According to one aspect of the present application, the present application provides a corrosion-resistant material for preparing a wafer chuck, which is prepared from the following raw materials in parts by weight: 70-90 parts of polyvinylidene fluoride grafted with perfluorohexyl side chains, 5-15 parts of modified boron nitride, and 5-15 parts of modified silicon carbide; the polyvinylidene fluoride grafted with perfluorohexyl side chains is prepared by grafting perfluorohexyl side chains to polyvinylidene fluoride using a monomer containing perfluorohexyl side chains as a grafting monomer.

[0008] Specifically, the present application specifically limits the composition and proportion of the corrosion-resistant material, uses a monomer containing perfluorohexyl side chains as a grafting monomer to graft perfluorohexyl side chains to polyvinylidene fluoride to obtain polyvinylidene fluoride grafted with perfluorohexyl side chains, which can improve the surface energy and chemical stability of polyvinylidene fluoride on the one hand, and can enhance the interaction between molecular chains and improve the barrier property, thereby improving the corrosion resistance.

[0009] Specifically, on the one hand, perfluorohexyl has extremely low surface energy and excellent chemical inertness, and after grafting the monomer containing perfluorohexyl side chains to the molecular chain of polyvinylidene fluoride, perfluorohexyl will be enriched on the surface of the material to form a structure similar to a "protective layer", effectively reducing the interaction between the surface of the material and corrosive media such as acids and bases, thereby improving the corrosion resistance of the material; on the other hand, the covalent bond between fluorine atoms and carbon atoms has higher bond energy and is not easily broken, so that the molecular chain structure of polyvinylidene fluoride grafted with perfluorohexyl side chains is more stable, which can resist the attack of corrosive media on chemical bonds, thereby improving the corrosion resistance.

[0010] Specifically, after introducing perfluorohexyl side chains, the entanglement degree between molecular chains is increased, the material as a whole is more compact, the entry of corrosive media into the interior of the material is reduced, a barrier effect is achieved, and the corrosion resistance is improved.

[0011] Optionally, the preparation method of the polyvinylidene fluoride grafted with perfluorohexyl side chains comprises the following steps:

[0012] Step 1: polyvinylidene fluoride is added to N,N-dimethylformamide, and stirred uniformly at a temperature of 60-80℃ to form a polyvinylidene fluoride solution;

[0013] Step 2: a monomer containing perfluorohexyl side chains and an initiator are added to the polyvinylidene fluoride solution and dispersed uniformly, and then the temperature is continued to be raised to 80-90℃ under nitrogen protection, and the reaction is continued for 6-8h;

[0014] Step 3: after the reaction is completed, alcohol precipitation is carried out, and then filtration, washing, and drying are carried out to obtain polyvinylidene fluoride grafted with perfluorohexyl side chains.

[0015] Optionally, the monomer containing perfluorohexyl side chain includes perfluorohexyl acrylate or perfluorohexyl methacrylate; the mass of the monomer containing perfluorohexyl side chain is 10-15% of the mass of the polyvinylidene fluoride;

[0016] The initiator includes azobisisobutyronitrile, and the mass of the initiator is 1-2% of the mass of the monomer containing perfluorohexyl side chain;

[0017] The mass fraction of the polyvinylidene fluoride solution is 15-20%.

[0018] Specifically, the preparation method and parameters of the polyvinylidene fluoride grafted with perfluorohexyl side chains are specifically limited to achieve the ideal grafting effect.

[0019] Optionally, the modified boron nitride is prepared by modifying boron nitride with a fluorine-containing organic compound, and the modified silicon carbide is prepared by modifying silicon carbide with a fluorine-containing silane coupling agent.

[0020] Specifically, the boron nitride is modified with a fluorine-containing organic compound, and the silicon carbide is modified with a fluorine-containing silane coupling agent, which can improve the dispersibility and compatibility of the boron nitride and the silicon carbide, and also synergistically improve the corrosion resistance of the material.

[0021] Specifically, the particle size of the boron nitride is 200 nm-2 μm, and the particle size of the silicon carbide is 80-500 nm.

[0022] Specifically, the modified boron nitride and the modified silicon carbide synergistically improve the corrosion resistance of the material, on the one hand, the modified silicon carbide is a nano-sized particle, which can fill the modified polyvinylidene fluoride matrix and possible micro-pores after being dispersed in the composite material, blocking the micro-channels; the modified boron nitride has a lamellar structure, and these lamellae can be stacked and staggered in the matrix, forming a large area of barrier to the corrosion medium, and the two work together to build a multi-level barrier structure to improve the corrosion resistance; on the other hand, the fluorine-containing groups of the two work together to hinder the contact of the corrosion medium with the material and the occurrence of chemical reactions, thereby improving the corrosion resistance.

[0023] Optionally, the preparation method of the modified boron nitride includes the following steps:

[0024] S01: Dissolve a fluorine-containing organic compound in an organic solvent to obtain a modifier solution; place boron nitride powder in an organic solution and ultrasonically disperse to obtain a boron nitride dispersion;

[0025] S02: Add the boron nitride dispersion to the modifier solution and stir under heating and reflux conditions for 4-6 h; after the reaction is completed, filter, wash and dry to obtain modified boron nitride.

[0026] Specifically, the fluorine-containing organic compound modifies the boron nitride, the fluorine-containing organic compound is attached to the surface of the boron nitride, the dispersibility and the compatibility of the boron nitride are improved, and the defect sites formed due to agglomeration are reduced; the layered structure of the modified boron nitride and the fluorine-containing groups on the surface of the modified boron nitride together enhance the barrier effect, and thus the corrosion resistance of the material is improved.

[0027] Specifically, the organic solvent includes toluene.

[0028] Optionally, the preparation method of the modified silicon carbide includes the following steps:

[0029] S1, the silicon carbide powder is placed in a mixed acid solution of hydrofluoric acid and nitric acid, stirred at 50-70°C for 10-30 min, after the reaction is completed, the deionized water is repeatedly washed until neutral; then it is placed in a sodium hydroxide solution, heated and stirred for 1-2 h, and then washed with deionized water until neutral to obtain the treated silicon carbide powder;

[0030] S2, the treated silicon carbide powder is dispersed in isopropyl alcohol, a fluorine-containing silane coupling agent is dissolved in a mixed solution of anhydrous ethanol and deionized water, the pH is adjusted to 3-5, stirred uniformly, and the dispersed silicon carbide powder is added;

[0031] S3, the reaction is stirred at room temperature for 2-4 h, after the reaction is completed, the modified silicon carbide is obtained by centrifugal separation, washing and drying.

[0032] Specifically, the silicon carbide powder is treated with acid, which can etch the surface of the silicon carbide, increase the surface roughness and expose more active sites, and after alkali treatment, the silicon carbide surface is more likely to form active hydroxyl groups, which is convenient for subsequent interaction with the fluorine-containing silane coupling agent.

[0033] Specifically, in the mixed acid solution of hydrofluoric acid and nitric acid, the volume ratio of hydrofluoric acid to nitric acid is 1:(2-3); the concentration of the sodium hydroxide solution is 1-2 mol / L.

[0034] Specifically, the fluorine-containing silane coupling agent modifies the silicon carbide, the siloxyl group (-Si-O-) at one end of the silane coupling agent can chemically react with the hydroxyl group (-OH) on the surface of the silicon carbide, and is firmly attached to the surface of the silicon carbide by chemical bonding, while the fluorine-containing group at the other end extends to the outside, which changes the properties of the silicon carbide surface, and thus improves the interfacial compatibility and dispersibility of the silicon carbide in the matrix; on the other hand, the fluorine-containing groups on the surface of the modified silicon carbide form a corrosion-resistant protective layer, the fluorine-containing groups can block or delay the contact of the corrosion medium with the inside of the material, and thus improve the corrosion resistance of the material.

[0035] Specifically, in the mixed solution of anhydrous ethanol and deionized water, the volume ratio of anhydrous ethanol to deionized water is (8-9):(1-2).

[0036] Specifically, the pH value is adjusted by dilute hydrochloric acid.

[0037] Optionally, the fluorine-containing organic compound includes perfluorooctanoic acid, perfluorosuccinic acid or perfluorodecanoic acid; the mass of the fluorine-containing organic compound is 2-5% of the mass of the boron nitride.

[0038] Optionally, the fluorine-containing silane coupling agent includes perfluorooctyltriethoxysilane, heptadecafluorodecyltriethoxysilane or tridecafluorooctyltrimethoxysilane; the mass of the fluorine-containing silane coupling agent is 3-5% of the mass of the silicon carbide.

[0039] According to another aspect of the present application, the preparation method of the corrosion-resistant material for preparing a wafer chuck is also provided, which comprises the following steps:

[0040] (1) The polyvinylidene fluoride grafted with perfluorohexyl side chains, modified boron nitride and modified silicon carbide are mixed in a high-speed mixer according to the weight ratio to obtain a premix;

[0041] (2) The premix is sequentially subjected to mixing, extrusion, granulation, drying and hot-pressing to obtain the corrosion-resistant material for preparing a wafer chuck.

[0042] Specifically, the rotation speed of the high-speed mixer is 1000-2000 rpm, and the mixing time is 10-30 min.

[0043] Optionally, the temperature for mixing, extrusion and granulation is 170-200°C; the drying temperature is 80-100°C; and the temperature for hot-pressing is 180-220°C, and the pressure is 5-10 MPa.

[0044] Specifically, the steps and process parameters of the preparation method of the corrosion-resistant material for preparing a wafer chuck are limited to obtain the corrosion-resistant material.

[0045] The beneficial effects of the present application include but are not limited to:

[0046] 1. According to the corrosion-resistant material for preparing a wafer chuck of the present application, the raw materials of the corrosion-resistant material for preparing a wafer chuck are limited, the polyvinylidene fluoride grafted with perfluorohexyl side chains serves as a matrix, which can effectively improve the acid and alkali resistance and corrosion resistance of the material, the modified boron nitride and the modified silicon carbide have good compatibility with the polyvinylidene fluoride grafted with perfluorohexyl side chains, the modified boron nitride and the modified silicon carbide are uniformly dispersed in the polyvinylidene fluoride matrix grafted with perfluorohexyl side chains, and the three together act to improve the corrosion resistance of the material.

[0047] 2. The corrosion-resistant material for preparing a wafer chuck according to the present application, wherein the boron nitride is modified by using a fluorine-containing organic compound, and the silicon carbide is modified by using a fluorine-containing silane coupling agent, so as to improve the dispersibility and compatibility of the boron nitride and the silicon carbide, and to improve the corrosion resistance of the material.

[0048] 3. The corrosion-resistant material for preparing a wafer chuck according to the present application, wherein the modified boron nitride and the modified silicon carbide are combined to form a multi-layer barrier structure, and the fluorine-containing groups of the two materials are combined to form a protective layer, so as to improve the corrosion resistance of the material.

[0049] 4. The preparation method of the corrosion-resistant material for preparing a wafer chuck according to the present application, wherein the preparation method is simple and easy to popularize. DETAILED DESCRIPTION

[0050] The present application will be described in detail below with reference to the examples, but the present application is not limited to the examples.

[0051] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application are purchased through commercial channels.

[0052] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art. The particle size of the boron nitride used in the examples and comparative examples of the present application is 1 μm, and the particle size of the silicon carbide is 100 nm.

[0053] Example 1

[0054] A preparation method of a corrosion-resistant material for preparing a wafer chuck:

[0055] (1) 70 parts of polyvinylidene fluoride grafted with perfluorohexyl side chains, 5 parts of modified boron nitride and 5 parts of modified silicon carbide are mixed in a high-speed mixer, the rotation speed of the high-speed mixer is 1000 rpm, and the mixing time is 10 min, to obtain a premix;

[0056] (2) The premix is sequentially subjected to mixing, extrusion, granulation, drying and hot-pressing molding, to obtain a corrosion-resistant material for preparing a wafer chuck; wherein the temperature for mixing, extrusion and granulation is 170°C; the drying temperature is 80°C; the temperature for hot-pressing molding is 180°C, and the pressure is 5 MPa.

[0057] The preparation method of the polyvinylidene fluoride grafted with perfluorohexyl side chains is as follows:

[0058] Step 1: polyvinylidene fluoride is added into N, N-dimethylformamide, the mass fraction of the polyvinylidene fluoride solution is 15%, and the polyvinylidene fluoride solution is uniformly stirred at a temperature of 60°C;

[0059] Step 2: add monomer perfluorohexyl acrylate containing perfluorohexyl side chain and initiator azobisisobutyronitrile into the polyvinylidene fluoride solution, the mass of the monomer containing perfluorohexyl side chain is 10% of the mass of the polyvinylidene fluoride, the mass of the initiator is 1% of the mass of the monomer containing perfluorohexyl side chain, uniformly disperse, continue to heat to 80℃ under nitrogen protection, and react for 6h;

[0060] Step 3: after the reaction is completed, alcohol precipitation is carried out, and filtration, washing and drying are performed to obtain polyvinylidene fluoride grafted with perfluorohexyl side chains;

[0061] The preparation of the modified boron nitride comprises the following steps:

[0062] S01: add fluorine-containing organic compound perfluorodecanoic acid into organic solvent toluene to obtain a modifier solution; place boron nitride powder into organic solution toluene, and uniformly disperse under ultrasonic to obtain a boron nitride dispersion liquid, the mass of the fluorine-containing organic compound is 2% of the mass of the boron nitride;

[0063] S02: add the boron nitride dispersion liquid into the modifier solution, stir and react under heating and refluxing conditions for 4-6h, after the reaction is completed, filtration, washing and drying are performed to obtain the modified boron nitride;

[0064] The preparation method of the modified silicon carbide comprises the following steps:

[0065] S1: place silicon carbide powder into a mixed acid solution of hydrofluoric acid and nitric acid, stir and react at 50℃ for 30min, after the reaction is completed, repeatedly wash with deionized water until neutral; then place into a sodium hydroxide solution, stir and react after heating for 1h, and then wash with deionized water until neutral to obtain treated silicon carbide powder;

[0066] S2: disperse the treated silicon carbide powder in isopropyl alcohol, dissolve fluorine-containing silane coupling agent perfluorooctyltriethoxysilane in a mixed solution of anhydrous ethanol and deionized water, the volume ratio of the anhydrous ethanol to the deionized water is 8:1, the mass of the fluorine-containing silane coupling agent is 3% of the mass of the silicon carbide, adjust the pH to 3 with dilute hydrochloric acid, stir uniformly, and then add the dispersed silicon carbide powder;

[0067] S2: stir and react at room temperature for 2h, after the reaction is completed, centrifugal separation, washing and drying are performed to obtain the modified silicon carbide.

[0068] Example 2

[0069] A preparation method of a corrosion-resistant material for preparing a wafer chuck:

[0070] (1) place 90 parts of polyvinylidene fluoride grafted with perfluorohexyl side chains, 15 parts of modified boron nitride and 15 parts of modified silicon carbide into a high-speed mixer, the rotating speed of the high-speed mixer is 2000rpm, and the mixing time is 30min to obtain a premix;

[0071] (2) the premix is sequentially subjected to mixing, extrusion, granulation, drying and hot-pressing forming to obtain a corrosion-resistant material for preparing a wafer chuck; wherein the temperature for mixing, extrusion and granulation is 200 DEG C; the drying temperature is 100 DEG C; the temperature for hot-pressing forming is 220 DEG C and the pressure is 10 MPa.

[0072] The preparation method of polyvinylidene fluoride grafted with perfluorohexyl side chains is as follows:

[0073] Step 1: polyvinylidene fluoride is added into N,N-dimethylformamide, the mass fraction of the polyvinylidene fluoride solution is 20%, and the polyvinylidene fluoride solution is uniformly stirred at 80 DEG C to form a polyvinylidene fluoride solution;

[0074] Step 2: perfluorohexyl methyl methacrylate containing perfluorohexyl side chains and initiator azobisisobutyronitrile are added into the polyvinylidene fluoride solution, the mass of the monomer containing perfluorohexyl side chains is 15% of the mass of the polyvinylidene fluoride, and the mass of the initiator is 2% of the mass of the monomer containing perfluorohexyl side chains, the mixture is uniformly dispersed, and then the temperature is continuously increased to 90 DEG C under nitrogen protection, and the reaction is carried out for 8 h;

[0075] Step 3: after the reaction is completed, alcohol precipitation, filtration, washing and drying are carried out to obtain polyvinylidene fluoride grafted with perfluorohexyl side chains;

[0076] The preparation of the modified boron nitride comprises the following steps:

[0077] S01: a fluorine-containing organic compound perfluorodecanoic acid is added into an organic solvent toluene to obtain a modifier solution; boron nitride powder is placed in the organic solution toluene, and ultrasonic dispersion is carried out to obtain a boron nitride dispersion liquid, and the mass of the fluorine-containing organic compound is 5% of the mass of the boron nitride;

[0078] S02: the boron nitride dispersion liquid is added into the modifier solution, and stirring is carried out under heating and reflux conditions for 6 h; after the reaction is completed, filtration, washing and drying are carried out to obtain modified boron nitride;

[0079] The preparation method of the modified silicon carbide comprises the following steps:

[0080] S1: silicon carbide powder is placed in a mixed acid solution of hydrofluoric acid and nitric acid, stirring is carried out at 70 DEG C for 10 min, after the reaction is completed, deionized water is repeatedly washed until neutral; then the silicon carbide powder is placed in a sodium hydroxide solution, stirring is carried out under heating for 1 h, and then deionized water is fully washed until neutral to obtain treated silicon carbide powder;

[0081] S2 disperses the treated silicon carbide powder in isopropyl alcohol, dissolves the fluorine-containing silane coupling agent tridecafluorooctyltrimethoxysilane in a mixed solution of anhydrous ethanol and deionized water, the volume ratio of anhydrous ethanol to deionized water is 9:2, the mass of the fluorine-containing silane coupling agent is 5% of the mass of the silicon carbide, adjusts the pH to 5 with dilute hydrochloric acid, stirs uniformly, and adds the well-dispersed silicon carbide powder;

[0082] S2 stirs at room temperature for 4h, after the reaction is completed, centrifugal separation, washing, and drying are performed to obtain the modified silicon carbide.

[0083] Example 3

[0084] A preparation method of a corrosion-resistant material for preparing a wafer chuck:

[0085] (1) 80 parts of polyvinylidene fluoride grafted with perfluorohexyl side chains, 10 parts of modified boron nitride, and 10 parts of modified silicon carbide are placed in a high-speed mixer for mixing, the rotation speed of the high-speed mixer is 1500 rpm, and the mixing time is 20 min to obtain a premix;

[0086] (2) The premix is sequentially subjected to mixing, extrusion, granulation, drying, and hot-pressing to obtain a corrosion-resistant material for preparing a wafer chuck; wherein the temperature for mixing, extrusion, and granulation is 180°C; the drying temperature is 90°C; the temperature for hot-pressing is 200°C, and the pressure is 5 MPa.

[0087] The preparation method of the polyvinylidene fluoride grafted with perfluorohexyl side chains is as follows:

[0088] Step 1: polyvinylidene fluoride is added to N,N-dimethylformamide, the mass fraction of the polyvinylidene fluoride solution is 15%, and the solution is stirred uniformly at 70°C to form a polyvinylidene fluoride solution;

[0089] Step 2: perfluorohexyl acrylate, a monomer containing perfluorohexyl side chains, and an initiator, azobisisobutyronitrile, are added to the polyvinylidene fluoride solution, the mass of the monomer containing perfluorohexyl side chains is 15% of the mass of the polyvinylidene fluoride, and the mass of the initiator is 2% of the mass of the monomer containing perfluorohexyl side chains, the solution is uniformly dispersed, and the temperature is continuously raised to 80°C under nitrogen protection, and the reaction is performed for 8h;

[0090] Step 3: after the reaction is completed, alcohol precipitation is performed, and the product is filtered, washed, and dried to obtain the polyvinylidene fluoride grafted with perfluorohexyl side chains;

[0091] The preparation of the modified boron nitride includes the following steps:

[0092] S01 adds a fluorine-containing organic compound, perfluorooctanoic acid, to an organic solvent, toluene, to obtain a modifier solution; places boron nitride powder in the organic solution, toluene, and uniformly disperses the boron nitride under ultrasonic waves to obtain a boron nitride dispersion liquid, the mass of the fluorine-containing organic compound is 4% of the mass of the boron nitride.

[0093] S02adding boron nitride dispersion liquid into modifier solution, stirring under heating reflux condition for 5h, after reaction, filtering, washing, drying to obtain modified boron nitride;

[0094] The preparation method of modified silicon carbide comprises the following steps:

[0095] S1placing silicon carbide powder into mixed acid solution of hydrofluoric acid and nitric acid, stirring at 60℃ for 20min, after reaction, repeatedly washing with deionized water until neutral; then placing into sodium hydroxide solution, stirring after heating for 1h, fully washing with deionized water until neutral, to obtain treated silicon carbide powder;

[0096] S2dispersing treated silicon carbide powder in isopropyl alcohol, dissolving fluorine-containing silane coupling agent perfluorooctyl triethoxysilane in mixed solution of anhydrous ethanol and deionized water, the volume ratio of anhydrous ethanol and deionized water is 9:1, the mass of the fluorine-containing silane coupling agent is 4% of the mass of silicon carbide, adjusting pH to 4 with dilute hydrochloric acid, stirring uniformly, and adding dispersed silicon carbide powder;

[0097] S2stirring at room temperature for 3h, after reaction, centrifugal separation, washing, drying to obtain modified silicon carbide.

[0098] Example 4

[0099] Example 4 is different from example 3 in that silane coupling agent KH550 is used instead of perfluorooctyl triethoxysilane in modified silicon carbide, and the rest is the same.

[0100] Example 5

[0101] Example 5 is different from example 3 in that the mass of monomer containing perfluorohexyl side chain is 25% of the mass of polyvinylidene fluoride, and the rest is the same.

[0102] Example 6

[0103] Example 6 is different from example 3 in that the mass of fluorine-containing organic compound is 10% of the mass of boron nitride, and the rest is the same.

[0104] Comparative example 1

[0105] Comparative example 1 is different from example 3 in that polyvinylidene fluoride is used instead of polyvinylidene fluoride grafted with perfluorohexyl side chain, and the rest is the same.

[0106] Comparative example 2

[0107] Comparative example 2 is different from example 3 in that boron nitride is used instead of modified boron nitride, and the rest is the same.

[0108] Comparative example 3

[0109] Comparative Example 3 differs from Example 3 in that modified silicon carbide is used instead of modified silicon carbide, and the rest are the same.

[0110] Comparative Example 4

[0111] Comparative Example 4 differs from Example 3 in that an equal amount of modified boron nitride is used instead of modified silicon carbide, and the rest are the same.

[0112] Comparative Example 5

[0113] Comparative Example 5 differs from Example 3 in that an equal amount of modified silicon carbide is used instead of modified boron nitride, and the rest are the same.

[0114] Experimental Example 1

[0115] According to GB / T 1040.2-2022, the corrosion-resistant materials prepared in Examples 1-6 and Comparative Examples 1-5 were made into samples, and the mechanical properties of the samples were tested. The test results are shown in Table 1.

[0116] Table 1: Mechanical property test results

[0117] Group Tensile strength (MPa) Elongation at break (%) Elastic modulus (GPa) Example 1 89.54 17.78 3.24 Example 2 89.47 17.54 3.15 Example 3 89.86 17.92 3.33 Example 4 84.65 14.24 3.10 Example 5 80.21 15.55 2.96 Example 6 82.10 13.69 3.02 Comparative Example 1 75.61 9.65 2.35 Comparative Example 2 78.41 10.32 2.57 Comparative Example 3 76.34 11.06 2.65 Comparative Example 4 75.68 11.88 2.77 Comparative Example 5 75.23 12.23 2.85

[0118] Experimental Example 2

[0119] According to GB / T 11547-2008, the corrosion-resistant materials prepared in Examples 1-6 and Comparative Examples 1-5 were made into samples, and the samples were immersed in 160℃ concentrated sulfuric acid solution (mass fraction of 85%) and 160℃ sodium hydroxide solution (0.1 mol / L) for 120 hours. The weight loss rate of the samples was measured. The test results are shown in Table 2.

[0120] Table 2: Corrosion resistance test results

[0121]

[0122]

[0123] From Tables 1 and 2, it can be concluded that the corrosion-resistant material for preparing a wafer chuck provided by the present application has good mechanical properties and corrosion resistance, and Example 3 is the best embodiment.

[0124] Example 4 uses common KH550 instead of perfluorooctyltriethoxysilane, resulting in a slight decrease in mechanical properties and a significant decrease in corrosion resistance, proving that fluorine-containing silane coupling agent can promote the uniform dispersion of silicon carbide in the matrix and has good compatibility with the matrix, and can block or delay the contact of corrosion medium with the internal material, improving the corrosion resistance of the material. Compared with Example 3, the mass of the monomer containing perfluorohexyl side chain in Example 5 increases, and the mechanical properties and corrosion resistance of the material decrease. The reason is that more grafted monomers will increase the degree of phase separation of the material, so the performance decreases; Compared with Example 3, the mass of the fluorine-containing organic compound for modifying boron nitride in Example 6 increases, and the mechanical properties and corrosion resistance of the material also decrease to a certain extent. The reason is that too much fluorine-containing organic compound will increase the surface polarity of the modified boron nitride, making it more prone to agglomeration, so the performance decreases.

[0125] In Comparative Example 1, polyvinylidene fluoride is used instead of polyvinylidene fluoride grafted with perfluorohexyl side chains, resulting in a significant decrease in material corrosion resistance and mechanical properties. In Comparative Examples 2 and 3, unmodified boron nitride and silicon carbide are used, and the material's corrosion resistance and mechanical properties also decrease significantly. In Comparative Example 4, only one kind of modified boron nitride is used, and the material's corrosion resistance and mechanical properties decrease more significantly. Therefore, Comparative Examples 2-4 can prove that the addition of modified boron nitride and modified silicon carbide has a good synergistic effect, and both are indispensable.

[0126] The above is only an embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. Various modifications and changes can be made to the present application by those skilled in the art. Any modification, equivalent replacement, improvement, etc. within the technical idea and principles of the present application should be included in the protection scope of the present application.

Claims

1. A corrosion resistant material for use in the manufacture of a wafer chuck, characterized by, The grafting polyvinylidene fluoride with perfluorohexyl side chain is prepared by the following raw materials: 70-90 parts of polyvinylidene fluoride grafted with perfluorohexyl side chain, 5-15 parts of modified boron nitride and 5-15 parts of modified silicon carbide, according to weight parts.

2. The corrosion resistant material for a wafer chuck according to claim 1, wherein The preparation method of the grafting polyvinylidene fluoride with perfluorohexyl side chain comprises the following steps: Step 1: polyvinylidene fluoride is added into N, N-dimethylformamide, and stirred uniformly at 60-80℃ to form a polyvinylidene fluoride solution; Step 2: monomer containing perfluorohexyl side chain and initiator are added into the polyvinylidene fluoride solution, and stirred uniformly, and then heated to 80-90℃ under nitrogen protection, and reacted for 6-8 hours; Step 3: after the reaction is completed, alcohol precipitation is carried out, and then filtration, washing and drying are carried out to obtain the grafting polyvinylidene fluoride with perfluorohexyl side chain.

3. The corrosion resistant material for use in manufacturing a wafer chuck according to claim 2, wherein, The monomer containing perfluorohexyl side chain includes perfluorohexyl acrylate or perfluorohexyl methacrylate; the mass of the monomer containing perfluorohexyl side chain is 10-15% of the mass of the polyvinylidene fluoride; The initiator includes azobisisobutyronitrile, and the mass of the initiator is 1-2% of the mass of the monomer containing perfluorohexyl side chain; The mass of the polyvinylidene fluoride solution is 15-20%.

4. The corrosion resistant material for use in a wafer chuck of claim 1, wherein, The modified boron nitride is prepared by modifying boron nitride with fluorine-containing organic compounds, and the modified silicon carbide is prepared by modifying silicon carbide with fluorine-containing silane coupling agents.

5. The corrosion resistant material for use in making a wafer chuck according to claim 4, wherein, The preparation method of the modified boron nitride comprises the following steps: S01: a fluorine-containing organic compound is added into an organic solvent to obtain a modifier solution; and boron nitride powder is dispersed in the organic solution to obtain a boron nitride dispersion liquid; S02: the boron nitride dispersion liquid is added into the modifier solution, and stirred under heating reflux condition for 4-6 hours; after the reaction is completed, filtration, washing and drying are carried out to obtain the modified boron nitride.

6. The corrosion resistant material for use in the preparation of a wafer chuck according to claim 5, wherein, The preparation method of the modified silicon carbide comprises the following steps: S1: silicon carbide powder is placed in a mixed acid solution of hydrofluoric acid and nitric acid, and stirred at 50-70℃ for 10-30 minutes; after the reaction is completed, deionized water is repeatedly washed until neutral; then the silicon carbide powder is placed in a sodium hydroxide solution, and stirred under heating for 1-2 hours; after the reaction is completed, the silicon carbide powder is washed with deionized water until neutral to obtain treated silicon carbide powder; S2: the treated silicon carbide powder is dispersed in isopropyl alcohol; a fluorine-containing silane coupling agent is dissolved in a mixed solution of anhydrous ethanol and deionized water, and the pH is adjusted to 3-5; the silicon carbide powder is added and stirred uniformly; S3: the reaction is carried out at room temperature for 2-4 hours; after the reaction is completed, centrifugal separation, washing and drying are carried out to obtain the modified silicon carbide.

7. The corrosion resistant material for use in making a wafer chuck according to claim 5, wherein, The fluorine-containing organic compound includes perfluorooctanoic acid, perfluorosuccinic acid or perfluorodecanoic acid; the mass of the fluorine-containing organic compound is 2-5% of the mass of the boron nitride.

8. The corrosion resistant material for use in making a wafer chuck according to claim 5, wherein, The fluorine-containing silane coupling agent includes perfluorooctyl triethoxysilane, heptadecafluorodecyl triethoxysilane or tridecafluorooctyl trimethoxysilane; the mass of the fluorine-containing silane coupling agent is 3-5% of the mass of the silicon carbide.

9. The method for producing an erosion resistant material for a wafer chuck according to any one of claims 1 to 8, characterized in that, The preparation method comprises the following steps: (1) according to the weight parts grafting polyvinyl fluoride with perfluorohexyl side chain, modified boron nitride, and modified silicon carbide are mixed in a high-speed mixer to obtain a premix; (2) the premix is sequentially subjected to mixing, extrusion, granulation, drying and hot-pressing to obtain a corrosion-resistant material for preparing a wafer chuck.

10. The corrosion resistant material for use in the preparation of a wafer chuck according to claim 9, wherein, The temperature for mixing, extrusion and granulation is 170-200 DEG C; the drying temperature is 80-100 DEG C; the temperature for hot-pressing is 180-220 DEG C, and the pressure is 5-10 MPa.